The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/microorganisms8050639
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins, Antimicrobial Peptides from Bacterial Origin: Overview of Their Biology and Their Impact against Multidrug-Resistant Bacteria

Abstract: Currently, the emergence and ongoing dissemination of antimicrobial resistance among bacteria are critical health and economic issue, leading to increased rates of morbidity and mortality related to bacterial infections. Research and development for new antimicrobial agents is currently needed to overcome this problem. Among the different approaches studied, bacteriocins seem to be a promising possibility. These molecules are peptides naturally synthesized by ribosomes, produced by both Gram-positive bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
173
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(226 citation statements)
references
References 177 publications
2
173
0
1
Order By: Relevance
“…Studies on the activity of bacteriocins, as an alternative to adjunctive therapy with antibiotics, and trials focused on probiotic bacteria are intensively conducted [31][32][33][34]. They concern mostly the bacteriocins of Gram-positive bacteria [35][36][37][38][39], but colicins and microcins are also tested as proteins with activity against pathogenic Gram-negative bacteria [40][41][42][43][44][45][46][47][48][49][50], including a few studies related to antibiotic-resistant strains [51,52]. However, nonclinical strains of animal origin, derived from farm animals that are particularly resistant to antibiotics, may reveal a distinct profile of sensitivity to bacteriocins.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the activity of bacteriocins, as an alternative to adjunctive therapy with antibiotics, and trials focused on probiotic bacteria are intensively conducted [31][32][33][34]. They concern mostly the bacteriocins of Gram-positive bacteria [35][36][37][38][39], but colicins and microcins are also tested as proteins with activity against pathogenic Gram-negative bacteria [40][41][42][43][44][45][46][47][48][49][50], including a few studies related to antibiotic-resistant strains [51,52]. However, nonclinical strains of animal origin, derived from farm animals that are particularly resistant to antibiotics, may reveal a distinct profile of sensitivity to bacteriocins.…”
Section: Introductionmentioning
confidence: 99%
“…Despite nisin remains the only bacteriocin approved as such for use as a preservative in food, LAB have attained a "Generally Regarded as Safe" (GRAS) status and bacteriocins in general have been shown to be safe for consumption because of their safe origin 23 . Bacteriocins are completely digested in the gastrointestinal tract, are resistant to the common thermal treatments for pasteurization or in some cases even sterilization, and are 10 3 -10 6 times stronger than several known antimicrobials (ampicillin, penicillin, chloramphenicol…) against pathogenic microorganisms, such as Listeria monocytogenes [24][25][26] . The use of bacteriocins in food preservation may also offer the benefit of meeting the consumers request for minimally processed food containing natural additives 27 .…”
mentioning
confidence: 99%
“…It is known that some LAB strains produce a wide variety of anti-pathogenic compounds, like bacteriocins, ethanol, organic acids, diacetyl, acetaldehydes, hydrogen peroxide (H 2 O 2 ), and peptides [42,43]. When we analyzed the antimicrobial spectrum against ten Gram-negative and Gram-positive bacteria, including closely related species and pathogens such as Salmonella enterica, Shigella sonnei, Escherichia coli, Enterobacter, Staphylococcus aureus, we observed that the isolates showed high inhibitory potential, as none had values below six and were defined as broad-spectrum (Figures 3 and 4).…”
Section: The Antimicrobial Profile Reveals That Inhibitory Activity Imentioning
confidence: 99%